The Woman Jesus Loved : Mary Magdalene in the Nag Hammadi Library and Related Documents - Marjanen, Antti, (Nag Hammadi and Manichaean Studies ;, 1996)
This is the first comprehensive study on Mary Magdalene in those second and third century Gnostic texts in which Jesus' most famous female follower gains a prominent position. Special attention is paid to the way Mary is presented in relation to other disciples, and to how her portrait pertains to gender imagery used in the writings. Detailed text analyses, based on a careful philological study, show that no uniform picture and use of the figure of Mary can be traced. Contrary to a common supposition, the book also demonstrates that the positive view of Mary displayed in the texts does not automatically imply a positive attitude towards women in general. The work provides a basis for all further discussion of Mary Magdalene in the Nag Hammadi and related documents.